Towards a municipal medical service
1924-10-02 1924 1920s 2 pages he considered the authorities at St. Mary’s were justified in sending a patient to the infirmary if they had no vacant beds, but Mrs. Drew ought not to have been moved in a taxi.” The Lambeth Coroner last April held two inquests on casualty cases refused admission to King’s College Hospital and carried elsewhere:— ‘‘This man,” he said, “with a broken thigh, a battered scull, and unconscious was driven to a hospital and kept there for an hour or two, then sent off to be jolted about in an ambulance on his way to the infirmary.” Manchester Guardian 25-4-24 In the other case: “Dr. Arthur Baly, medical superintendent at the Infirmary said the patient was unconscious and suffering from concussion of the brain. He died on Sunday. His removal from the hospital was the worst thing that could have been done for him, as he needed absolute rest.” ibid Inefficiency of the voluntary hospitals lies not in hospitals themselves but in the system. Hospitals reduced to undignified and sometimes anti-civic expedients to raise money, lotteries; organised tuft-hunting; sale of honours. Labour’s Way. All over the country poor-law infirmaries are half empty. It is estimated that there are 18,000 beds available in these institutions. In Bradford, the Royal Infirmary (voluntary: and note the “Royal”) had only 200 beds for a population of 300,000. Corporation took over Poor Law hospital from the Guardians, turned it into a fully-equipped civic general hospital with 1,000 beds. Poor law patients are still accommodated in the hospital and receive the same treatment as civic patients. Figures show success of experiment:— Manchester Guardian 5-7-23 Admissions in Poor law. Civic. Total. 1920 2,290 1,514 3,804 1921 1,869 2,613 4,482 1922 1,559 3,582 5,141 1923 1,505 4,103 5,608 British Medical Journal 3-5-24 Commenting on these figures “Sir Thomas Neil urged that a scheme for hospital reform should be prepared and presented to the Ministry of Health. The example of Bradford should be followed by the municipalities throughout the country.” Times 30-4-24 Conclusion. The establishment of Municipal general hospitals to supplement the work of existing hospitals is an urgent and immediate necessity. The co-ordination and amplification of all municipal and medical services is called for. Why not Municipal general clinics as well as Municipal general hospitals? Children may receive medical attention from Municipal services from birth to school leaving age, when they are turned over to private practitioners. Adolescence is a dangerous time to change doctors. Municipal general clinics would command the services of a number of specialists to whom exceptional cases could be turned over without delay. Printed by FROWDE & Co. (T.U. all Depts.), 242-244, Old Kent Road, S.E.1 292/840/1/1